Kualitas Pelayanan Publik Pada Kantor Kelurahan Pematang Reba Kecamatan Rengat Barat Tahun 2020 - Surya Akbar (JIAGANIS, 2022)
ABSTRACTThis study aims to determine the quality of public services at the Pematang Reba Village Office, West Rengat District, and the supporting factors and barriers to service in the Pematang Reba Village Office, Rengat Barat District. This research method is a descriptive study with a qualitative approach. Qualitative descriptive research is research that aims to describe and describe events and phenomena that occur in the field and present data in a systematic, factual and accurate manner regarding facts or phenomena that occur in the field. Data collection was done by using observation, interview and documentation techniques. Researchers used source triangulation to check the validity of the research data. Data analysis in this study used three components consisting of data reduction, data presentation and conclusion drawing. The results of this study indicate that the quality of public services in the Pematang Reba Urban Village Office, West Rengat District has been applied to the dimensions of Tangibel, Realiability, Responsiviness, Assurance and Emphaty along with its indicators. However, there are several indicators that have not worked according to the wishes of the community, including the inconvenience of service places including incomplete facilities and infrastructure, not yet skilled employees in using service aids, and employee unfriendliness in the service process.The inhibiting factor for the implementation of public services at the Pematang Reba Village Office, West Rengat District is the lack of staff resources and the lack of infrastructure. While the supporting factor is the enthusiasm given by employees to one another, holding a coordination meeting or some kind of evaluation every three months and then giving the planting of awareness to serve the community sincerely and according to one's heart. Another supporting factor is the facilities in the form of tools to facilitate the service process.